Impact of ENSO (el Niño southern oscillation) and sowing date on soil water storage evolution in corn (Semiárida, 2018)
Agricultural production in the central semiarid region of Argentina (CSRA) is strongly limited by the availability of water, which is associated with the occurrence of El Niño southern Oscillation (ENSO).The aim of the work was to analyze the evolution of water stored in the soil (WSS) in different phenological stages of the corn (Zea mays L.) for early spring (ESS) and late (LSS) sowings under different ENSO conditions. To achieve the objective, daily WSS was calculated throughout the maize crop cycle in ESS (1 October) and LSS (1 December) for the period between 19/50/2015 using the Agroagua software version 4.1. The results showed that LSS had higher WSS levels during the critical period of the crop (15 days before and 15 days after flowering) and 30 days after, than in ESS. In LSS the highest levels of WSS during the critical period of the crop were reached in La Niña years, while in ESS they were reached in El Niño years. The highest levels of WSS would be associated with higher crop productivity. However, to confirm the latter, field trials or simulations with programs to estimate the yield should be conducted.
Keywords: MEI; crop management; water balance; ENSO